Tensile properties of domestic Al2O3f/Al2O3 composite at room temperature and 1000 ℃ - ZHANG Ke; XU Ping; ZHANG Chao; LI Chenchen; YING Wenqing; XING Ning; LI Mei; ZHANG Chengyu (Cailiao gongcheng)
Continuous alumina fiber reinforced alumina composite （Al2O3f/Al2O3） is an ideal material for developing high-performance aero-engine hot section components. In this study， the room-temperature and 1000 ℃ tensile mechanical properties of domestic Al2O3f/Al2O3 are investigated. The microscopic morphology and fracture morphology of tensile specimens are observed by SEM. The microstructure is observed by TEM. The tensile strength is analyzed using the Weibull distribution， and the fiber/matrix interfacial shear strength is obtained by the fiber push-in method. The results show that the room-temperature tensile strength of domestic Al2O3f/Al2O3 is （257±31） MPa while the tensile strength at 1000 ℃ is 78% of room temperature strength， reaching the level of foreign Nextel610/Al2O3. The interfacial bonding is the main factor affecting the tensile strength. High tensile strength with low interfacial bonding strength， results in long and dispersed fiber pull-out. Low tensile strength with high interfacial bonding strength， results in fiber bundle breakage and shorter fiber pull-out.